The Effect of Pedagogic Competence and Professional Competence on the Performance of PAI Teachers at SMAN 3 Pagar Alam City - Wulan Sari (South Sulawesi Education Development (SSED), 2024)
The purpose of this study was to determine how much influence pedagogic competence (X1) and professional competence (X2) have on the performance of Islamic religious education teachers (Y) at SMA Negeri Pagar Alam Kota. The sample used was five certified teachers using purposive sampling. The techniques used to obtain and collect the necessary data are questionnaire and documentation methods. Preparation using quantitative methods with associative approach techniques. Using SPSS V.22, test the hypothesis using partial Test (t), simultaneous Test (F), and coefficient of determination (R2). The results showed that performance was positively and significantly influenced by pedagogical competence. Teacher performance is positively and significantly influenced by professional competence. Professionalism and pedagogical skills have a significant and beneficial impact on performance. It is hoped that the results of this study can provide information to educational institutions, educational services, and the government to improve professional competence and pedagogic competence to improve teacher performance.